Arabica Coffee Development Model in Alleviating Poverty in West Sumatra - Hasnah Hasnah; Rika Hariance; Muhammad Hendri (International Journal of Agricultural Sciences, 2022)
Arabica coffee has promising market potential in the world market, which reaches 85%. However, national coffee commodity production has been dominated by Robusta coffee which reaches 90% and only 10% of production is Arabica coffee. Given the opportunity of this Arabica coffee market, the West Sumatra government tried to develop this type of coffee. Solok Regency is an area that develops Arabica Coffee rapidly so that it can become the second largest Arabica coffee growing area in the last 3 years. The study aims to: (1) Measure the proportion of smallholder farmers whose income is below the poverty line and the severity of the poverty situation; (2) Analyze the influence of economic and non-economic factors on the poverty rate of coffee farmers. This research will be conducted in Solok Regency which is selected purposively with the consideration that this area has a high poverty rate and has a rapid growth in arabica coffee growing area. The results showed that the poverty rate of Arabica coffee farmers is quite large with a Head-count index of 0.50 meaning that as many as 50% of farmers have incomes that are below the poverty line. Arabica coffee farmers who are members of cooperatives have a higher poverty rate compared to non-cooperative farmers both from the Headcount Index and from the Poverty Gap Index and Poverty Severity Index. This is because cooperative farmers have no other source of income and are very dependent on coffee farming on narrow land. Factors that affect the poverty rate of Arabica coffee farmers are assets and being members of cooperatives. The existence of cooperatives will be able to increase opportunities for farmers to gain access to economic facilities, one of which is access to financing sources, so that it will be able to encourage farmers to develop their businesses and open new businesses to increase their income.To increase the income of Arabica coffee farmers, there needs to be policies to encourage farmers to open other businesses so as to increase farmers' incomes. Diversification of business becomes very important because it will be able to help farmers to get out of poverty.